Effects of open and closed tracheal suctioning on pain in mechanically ventilated patients - Fatemeh Khayer; Somayeh Ghafari; Mahmoud Saghaei; Ahmadreza Yazdannik; Vajihe Atashi (Wolters Kluwer Medknow Publications, 2020)
Background: Painful care procedures are the most common cause of stress in patients admitted to Intensive Care Units (ICUs). Tracheal suctioning is the most painful experience for ICU patients. The present study was conducted to compare open and closed endotracheal suctioning in terms of their effect in pain in mechanically ventilated patients. Materials and Methods: The present clinical trial recruited 70 mechanically ventilated patients with tracheostomy in 2019. The eligible patients were randomly divided into open and closed suctioning groups. The pain was measured in the patients using the Critical Pain Observational Tool (CPOT) before and during suctioning as well as 10 and 30 min later. The data were analyzed using the repeated measures Analysis Of Variance (ANOVA), paired t-test, and Chi-squared test. Results: The pain score was significantly higher in the open suctioning group during (t = 2.59, p = 0.01) and 10 min after suctioning (t = 3.02, p = 0.004). No significant differences were observed in the pain score between the two groups 30 min after suctioning (t = 0.32, p = 0.75). The post hoc Least Significant Difference (LSD) test showed that the CPOT scores 10 min after suctioning was significantly higher than that before suctioning and significantly lower than that during suctioning (p = 0.001). The CPOT score 30 min after suctioning was also significantly lower than that 10 min after suctioning (p < 0.001). Conclusions: The present findings suggested a lower pain in the patients with closed suctioning compared to those with open suctioning.